Association Between the Japanese Version of Montreal Cognitive Assessment Tasks and Driving as the Primary Mode of Transport Among Community-Dwelling Older Adults. - Nakajima, Yuya; Onishi, Hidenori; Mizukami, Yasutaka; Okamoto, Tomoko; Inoue, Taisei; Koujimoto, Akemi; Konoshita, Naohiro; Tanaka, Tokuharu; Matsunaga, Akiko; Kubota, Masafumi; Ikawa, Masamichi; Hori, Hideaki; et al. (Canadian Geriatrics Journal, 2026)
Background: Deciding whether to continue driving or transition to alternative means of transportation is a challenging issue for older adults in preventive care settings. This study aimed to identify potential associations between the Japanese version of the Montreal Cognitive Assessment (MoCA-J) and driving as the primary mode of transport among older adults. Methods: The participants of this cross-sectional study were community-dwelling older adults participating in a long-term preventive care program. Participants were divided into two groups (DRIVING or OTHER) based on their questionnaire response regarding the main mode of transport used when going out, where the OTHER group included all participants who selected any other mode than a car driven by themselves. Cognitive function was measured using 13 MoCA-J tasks. Binary logistic regression analysis was used to identify associations between MoCA-J results and inclusion in the DRIVING group. Results: Among the 199 participants, 156 were categorized into DRIVING group and 43 into OTHER group. The DRIVING group showed significantly higher task achievement rates than the OTHER group in trail-making, digit span, and phonemic verbal fluency tests. Of these, only the trail-making test results were associated with inclusion in the DRIVING group (odds ratio, 2.82; 95% confidence interval, 1.22–6.51; p =.016). Conclusions: The trail-making task of MoCA-J may assist health-care professionals in providing driving guidance to older adults.